PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPA DENGAN MODEL LEARNING STARTS WITH A QUESTION SISWA KELAS VII - Artono Artono (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
The objective of this study is to improve the activity and the results of science learning at VII grade students by using the Learning Starts with a Question model in SMP N 11 Yogyakarta in the academic year 2013/2014. It is obtained there are several problems that students of VII grade SMP N 11 Yogyakarta face. This study uses Classroom Action Research (CAR). The data was collected through observation, interviews, documentation, and test. The results showed that after using model ‘Learning Starts with a Question’ in class VII A of SMP Negeri 11 Yogyakarta, students’ activity and learning outcome increased. This is indicated by an improvement in the average percentage of student learning activity observation sheet for each cycle, the average of the activity indicator in the first cycle is 74% and it increased 8% to 82% in the second cycle. The average of science learning outcomes for students before the treatment is 53.75, it becomes 65.71 in the first cycle and 78.28 on the second cycle. Most students pass the passing grade (KKM). In the first cycle, there are 16 students who achieve the score above the passing grade (KKM) with the percentage of 45.71%, while on the second cycle it increased to 27 of students or 77.14%.